RANCANG BANGUN ALAT DETEKSI WARNA UNTUK MEMBANTU PENDERITA BUTA WARNA BERBASIS MIKROKONTROLER AVR ATMEGA16 - Saiful Widianto; Kusworo Adi; Hernowo Danusaputro (Youngster Physics Journal, 2013)
Primary colour detection system made by using colour censor for aquisition and controlled by microcontroller AVR ATMega16 to grouping into various colour. This system consists of hardware likely IC ISD 2590, LCD M1632, Mini microphone, Mini speaker, and Microcontroler AVR ATMega16. Softwere in microcontroler use language C with softwere C Avr and detection result display displayeds in lcd M1632.Primary colour detection system uses colour censor TCS3200 the tension product result linear and calibrated with ingredient colour frequency. primary colour detection system uses colour censor TCS3200 the tension product result linear and calibrated with ingredient colour frequency. Ingredient colour detection that measuresed based on value RGB use push button as electric switch on-off to light led white as white iight source, and colour censor TCS3200 functioned to get light to reflection from ingredient that hitted light. in display lcd be got measurable frequency value magnitude as according to value Red Green Blue (RGB), and sound wave is taked by mini speaker that come from system IC ISD2590 all integrations with mikrokontroler AVR ATMega16.Keyword : Microcontroler AVR ATMega16, IC ISD2590, LCD M1632, Colour Censor TCS3200